To the Fiftieth Anniversary of the Department of Algebra and Mathematical Logic of Kyiv Taras Shevchenko University - Bezushchak, O.O.; Drozd, Yu.A.; Gorodniy, M.F.; Petravchuk, A.P.; Sushchanskiy, V.I. (Algebra and Discrete Mathematics, 2010)
History of algebraic research in Kyiv University starts in 1902 when

Professor D. Grave who was a pupil of the St.Petersburg mathematical

school started his work at Kyiv University. After moving to Kyiv Professor

Grave began intensive research in the modern at that time branches

of mathematics such as group theory, Galois theory, theory of algebraic

numbers.